Case Study of Today's Automotive Dealerships: Introduction and Delivery of Advanced Driver Assistance Systems. Issue 1 (2017) - Abraham, Hillary; McAnulty, Hale; Mehler, Bruce; Reimer, Bryan
Vehicle manufacturers have developed advanced driver assistance systems (ADASs) to reduce driver workload and enhance safety. The delivery of these systems to consumers occurs through dealerships not owned by manufacturers. Limited research is available on how dealerships provide consumers with information and training on ADASs. In an exploratory study seeking information on new safety technologies, semistructured blind interviews of salespeople at 18 Boston, Massachusetts, area dealerships were conducted in the context of potential vehicle purchase across six vehicle brands. Although some dealerships were making concerted efforts to introduce and educate customers on ADASs, a number of salespeople interviewed were not well positioned to provide adequate information to their customers. In select instances, salespeople explicitly provided inaccurate information on safety-critical systems. The dealerships in the sample that represented mass-market brands (Ford and Chevrolet) were the poorest performers. Sales staff at Subaru dealers were well trained and had print and digital content to drive consumer engagement. Educational staff, or "geniuses, " at BMW dealers presented a potentially innovative way of segmenting the sales process from technology education. In the absence of some technology introduction and education at dealerships, consumers may remain underinformed or misinformed about the disruptive safety technologies that are rapidly being introduced across the vehicle fleet.